Production of extracellular proteins and cellulases by different isolates of Chaetomium globosum Krunze ex. Fr. - and K.D. SRIVASTAVA, SHAIK KHAYUM AHAMMED, RASHMI AGGARWAL* (Indian Phytopathology, 2008)
Chaetomium globosum has been identified as a potential antagonist of several seed borne and soil borne pathogens. Nine isolates of C.globosum were examined for the presence of extra cellular proteins in culture filtrate by SDS-PAGE. All the isolates were found to be different with respect to the profile of extra cellular proteins. The dendrogram showed that isolates Cg2 and Cg3 resembled each other, while Cg5 and Cg6, and Cg7, Cg8 and Cg9 were similar and showed high degree of similarity forming a separate group. Isolates Cg1 and Cg4 did not resemble any other isolate. The six isolates i.e., Cg1, Cg2, Cg3, Cg4, Cg5 and Cg6, which showed more number of bands in protein profile were further screened for the production of cellulases in culture filterate. Filter Paper Activity (FPase) of these isolates revealed that maximum activity was observed after 9 days of incubation. The isolate Cg2 had the maximum activity (0.79 IU/ml) while Cg5 had least activity (0.48IU/ml). Similarly, the carboxy methyl cellulase (CMC-ase) activity was maximum in case of isolate Cg2 and productivity of cellobiase was also maximum in case of isolate Cg2 and least in Cg1 on ninth day of incubation.